On Semigroup Ideals and Generalized Two Sided Reverse α -3- Derivation in Prime Near-Ring - Saed, Ikram (Al-Qadisiyah Journal of Pure Science, 2020)
Let N be a near –ring and is a mapping on N .In this paper, we will introduce the notions of two sided reverse -3-derivation and generalized two sided reverse -3-derivation of N . Then we will study commutativity of N under some conditions determined on semigroup ideals of N .